Look in to look out: strategy and family business identity during COVID-19 - Rebecca Alguera Kleine; Bingbing Ge; Alfredo De Massis (Small Business Economics, 2023)
Abstract COVID-19 challenges the value systems of family firms and urges them to adapt their behaviors, affecting their identities. This study aims to explore how and why family businesses strategically respond to challenges to their identity during COVID-19 . Based on a qualitative case study of six German family firms, we propose a process model of family business identity variations during COVID-19 with three propositions, highlighting the interplay between strategy and identity. Counterintuitively, we found that an exogenous shock like COVID-19 can have a positive effect on family business identity, leading to identity clarification or consolidation. We contribute to the growing stream of research investigating the impact of COVID-19 on SMEs, as well as research on family business identity heterogeneity and organizational identity literature by illustrating the interplay between strategy and identity. @Plain English Summary: The silver lining of COVID-19 for family business identity: COVID-19, as one recent exogenous shock, posed a strong challenge for family businesses. However, little is known about how family businesses deal with exogenous shocks that force strategic responses and thus challenge family businesses to question “who are we as an organization”. In this study, we investigated how strategic responses induced by COVID-19 affected the identity of German family firms. Counterintuitively, our study reveals that COVID-19 provided an opportunity for family business identity consolidation. It highlights how a firm's unique identity stemming from the closeness with the family can serve as a guidance for strategy-making during COVID-19. Specifically, the study unearths that, when facing the uncertainty of external challenges like COVID-19, the competing family business goal systems are challenged, providing an opportunity for family business owners to refine and re-define the identity of the family businesses. Overall, it thus shows that exogenous shocks can have a positive impact on the family businesses' identity, by leading to a consolidation of an already existing identity, as well as to a clarification of a previously unclear identity.
Additional information: D21;L21;L26
Keywords: 330; Family business identity; COVID-19; Strategy; Exogenous shock; Multiple case study; Mittelstand